(untitled) (Baghdad Science Journal, 2025)
Breast tumor patients generally have more oxidative stress than normal females. This was clear from non significant decrease in RBCs and serum of GSH-Pex activity in all groups of patients. The study had found that free radicals in malignant breast tumors were higher than benign tumors; therefore the GSH- Pex might be used as markers for prognosis of the disease.